Obesity Stigma Among Healthcare Workers in a Teaching Hospital in Saudi Arabia - Ahmed S. Bahamdan; Marwa M. Shafey; Assim M. Alabdulkader; Adam F. Aldhawyan; Khalid S. Alharkan; Omar K. Almohaimeed; Mohammad J. Holdar (Journal of Primary Care & Community Health)
Background: Obesity is a significant public health issue in Saudi Arabia. Rising obesity rates increase the risk of weight bias and stigma, even among healthcare workers. Objectives: This study assesses weight stigma in healthcare workers, with findings intended to inform strategies for creating a more supportive healthcare environment for patients with obesity. Methods: This cross-sectional study was conducted in a university hospital in the Eastern Province of Saudi Arabia. Healthcare workers completed self-administered questionnaires, including the Attitudes toward Obese Persons Scale (ATOP) and the Beliefs about Obese Persons Scale (BAOP), which assess levels of positive attitudes and beliefs about obesity, respectively. Data were analyzed using SPSS. Results: The study included 266 healthcare workers (HCWs), mean age 33.21 years, with 54.5% female. The ATOP mean score was 64.4, and BAOP mean score was 18.3, indicating moderate negative attitudes and beliefs toward obesity. Significant differences in ATOP scores were found based on age, patient interactions, and years of experience. Discussion Our study aligns with international findings, revealing significant weight stigma among healthcare workers in Saudi Arabia. Such stigma can negatively impact patient care, leading to biased treatment and poorer health outcomes. Societal norms and personal biases contribute to this stigma, despite misconceptions regarding its supposed motivational effects. Addressing this requires comprehensive training and education for healthcare providers. Policymakers should include weight bias education into medical curricula and establish anti-discrimination policies to promote inclusivity and respect. Conclusions: Our study highlights obesity stigma among Saudi healthcare workers and the need for targeted interventions. Creating a supportive, nonjudgmental environment can enhance patient-provider relationships and improve healthcare outcomes for individuals with obesity.